2020
DOI: 10.1111/andr.12778
|View full text |Cite
|
Sign up to set email alerts
|

Teratozoospermia: Its association with sperm DNA defects, apoptotic alterations, and oxidative stress

Abstract: This study was carried out to evaluate the level of nuclear sperm DNA damage in men with isolated polymorphic teratozoospermia and examining its relationship with apoptosis and oxidative stress. A total of 89 subjects were divided into two groups: men with isolated teratozoospermia (n = 69) and men with normal semen parameters (n = 20) as controls. Sperm DNA breaks were determined by using acridine orange staining. The proportion of viable spermatozoa with mitochondrial transmembrane depolarization was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…The correlations between sperm morphology, sperm DNA integrity and oxidative balance have been recently investigated [ 13 , 27 , 28 ]. In this context, it has been observed that several conditions including inflammatory and infectious diseases may increase systemic and seminal OS, thus leading to impaired sperm morphology [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The correlations between sperm morphology, sperm DNA integrity and oxidative balance have been recently investigated [ 13 , 27 , 28 ]. In this context, it has been observed that several conditions including inflammatory and infectious diseases may increase systemic and seminal OS, thus leading to impaired sperm morphology [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Agarwal et al suggested that spermatozoa with pathological morphology and activated leukocytes were the main source of ROS over-production in semen and that OS might further lead to structural cell defects [ 14 ]. Similarly, Ammar et al found that ROS generated from morphologically abnormal spermatozoa along with impaired seminal antioxidant defence may eventually induce many changes in sperm cells, thus including membrane and DNA damage and cell death [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, cytogenetic investigations of severe teratozoospermia represented one of the most productive areas in the field of male infertility and assisted conception. [1][2][3][4] The effect of isolated teratozoospermia is controversial, with studies showing both improved 5 and worsened [6][7][8][9] assisted reproductive technology (ART) fertilization and/or pregnancy rates with in vitro fertilization outcome (IVF).…”
Section: Introductionmentioning
confidence: 99%